Kontrak Cirebon-VOC Tahun 1699: Peran VOC dalam Menjaga Stabilitas Keamanan Cirebon - Tendi Tendi (Socio Historica: Journal of Islamic Social History, 2022)
During the second half of the seventeenth century, the political constellation of Java changed drastically. The dominance of Mataram in Priangan, which was previously strong, was replaced by the superiority of Banten which carried out military expansion to a number of Priangan areas, including Cirebon. However, the domination did not last long because in 1680, the Cirebon princes were more inclined to ally with VOC than Mataram or Banten. After his position was strengthened in Cirebon, the turmoil of disputes which based on the desire for power emerged from within the kraton, and grew even more after the death of Sultan Sĕpuh I in 1697. To maintain the rush en order of the regions under his supervision, VOC helped mediate the conflict and set Contract of August 4, 1699 as a solution to the problem. The Cirebon-VOC contract in 1699 was written manually and still preserved today. Through the contract, VOC regulated the nobility degree of the three Cirebon rulers on the basis of applicable customs and established other rules to eliminate competition as the seed of conflict. Sepanjang paruh kedua Abad XVII, konstalasi politik Tanah Jawa berubah secara drastis. Dominasi Mataram di Priangan yang sebelumnya kokoh, berganti dengan kedigdayaan Banten yang melakukan ekspansi militer ke sejumlah daerah Priangan, termasuk di antaranya Cirebon. Namun, dominasi itu tidak berlangsung lama karena memasuki tahun 1680, para pangeran Cirebon lebih condong untuk bersekutu dengan VOC ketimbang Mataram ataupun Banten. Setelah kedudukannya semakin kokoh di Cirebon, gejolak perselisihan yang dilandasi oleh keinginan berkuasa justru muncul dari internal istana, dan semakin membesar pasca wafatnya Sultan Sĕpuh I pada 1697. Untuk tetap menjaga rush en orde wilayah yang berada di bawah pengawasannya, VOC turut menengahi konflik dan menetapkan Kontrak 4 Agustus 1699 sebagai solusi permasalahan. Kontrak Cirebon-VOC tahun 1699 ditulis secara manual dan masih tersimpan hingga sekarang. Melalui kontrak itu, VOC mengatur derajat kebangsawanan ketiga penguasa Cirebon dengan dasar adat yang berlaku dan menetapkan aturan lainnya untuk menghilangkan persaingan yang merupakan benih konflik yang terjadi di tengah para penguasa tertinggi Cirebon.